DEIXIS ANALYSIS OF MAIN CHARACTER IN RAYA THE LAST DRAGON 2021 MOVIE - Arfala Norma , Anggi Dwi Arfala Norma; Ambalegin, Ambalegin (Universitas Putera Batam, 2023)
The objective of this research was to figure out how deixis was used in the movie that released in 2021, entitle “Raya and the Last Dragon”. Additionally, this research was also concerned with the type of deixis. The researchers employed a qualitative descriptive research method in this research. The source of data for the research is the movie's main character. The data was gathered using an observational method and a note-taking technique. The pragmatic competence-in-equalizing were implemented to analyse the data. The results obtained from this research define the numerous types of deixis, such as personal deixis, place deixis, temporal deixis, social deixis, and discourse deixis by using Levinson's (1983) theory. According to the findings, the following types of deixis exist: person deixis, place deixis, time deixis, social deixis, and discourse deixis. Person deixis accounted for 11 data, place deixis accounted for 3, time deixis accounted for 1, social deixis accounted for 2, and discourse deixis accounted for 4. Thus, in the movie Raya and the Last Dragon, person deixis was determined to be the most prevalent type of deixis.